The Influence of Celebrity Endorsement on Consumer’s Attitude: A Study Case of Smartphone Brands in Jakarta, Indonesia - Melati, Ina; Indira Budiwan, Teddy; Sarjono, Haryadi (International Journal of Engineering and Technology, 2018)
This study analyzes the effect of celebrity endorsement on consumer’s attitude towards social media advertising as well as the effect of consumer’s attitude towards social media advertising on consumer’s purchase intention of smartphone brands in Jakarta. A survey was conducted on 404 university students in Bina Nusantara University. After conducting exploratory factor analysis (EFA) and multiple-regression analysis, the result indicates that consumer’s attitude towards social media advertising is positively affected by 4 factors: celebrity trustworthiness, celebrity liking, celebrity match-up with product and celebrity familiarity. Attitude towards social media advertising also has a positive impact on consumer’s purchase intention of smartphone brands in Jakarta.
Keywords: Celebrity Endorsement; Consumer’s Attitude towards Social Media Advertising; Purchase Intention; Smartphone Brands